Expensive living: the Greek experience under the euro - Theodore Pelagidis; Taun N. Toay (Levy Economics Institute of Bard College, 2006)
Apart from its widely accepted direct advantages, the introduction of the euro has been accompanied by a surge of inflation in most of the EU member states. At the same time, wages-in part, wages of the unskilled-are relatively losing ground, while the purchasing power of the average European seems also to have weakened since the introduction of the single currency. In this paper we deal with five relevant central issues to interpret expensiveness in Greece. First, we examine to what extent recent inflation trends are attributable to the constraints imposed by the monetary union-namely negative demand disturbances in certain Greek regions. Second, we investigate to what extent these patterns are also due to the adoption of the euro-including conversion period effects-over product market and other domestic rigidities. Third, we investigate the impact of seasonal effects on inflation, in the context of the Greek socalled traditional petit-bourgeois capitalism. Fourth, we explore the extent to which unemployment is another factor that drives wages and purchasing power down. Fifth, we apply the Balassa-Samuelson effect to see whether it constitutes the culprit for price hikes in nontradable products in particular. We find that all the aforementioned factors contribute to the Greek expensiveness.
Keywords: E31; 330; Inflation; Greek Economy; Balassa-Samuelson Effect; Seasonal Effect; Product Markets; Unemployment; Monetary Union